The Effect of N-Acetylcysteine on Oxidant/Antioxidant Status in Irradiated Rats - Özçelik, Mehtap; Erısır, Mine; Guler, Osman; Baykara, Murat (My University, 2020)
N-Acetylcysteine (NAC) is both a strong antioxidant and a glutathione precursor. The effect of NAC on the oxidant/antioxidant status of some tissues of the irradiated rats was investigated. Twenty one rats were assigned to 3 groups; the control group, the irradiation group, for which physiological saline solution was administered as i.p. for three days and then, 9 Gy gamma irradiation was applied, and 3rdirradiation + NAC group for which NAC was adminis-tered as i.p. for three days as 300 mg/kg body weight and then the same dose of irradiation was applied. Upon irradia-tion, the increase determined in malondialdehyde (MDA) was significant in the liver, kidney, and brain tissues of the rats (P?0.05). While glutathione peroxidase (GSH-Px) activity decreased in all of the tissues and superoxide dismutase (SOD) activity only in the liver (P?0.01), glutathione (GSH) levels significantly increased in the kidney and ovarium tissues (P?0.001). While NAC administration returned the increased MDA levels in the kidney and brain as a result of irradiation to normal levels (P?0.05), it was determined that it did not return the increased MDA levels in the liver tissue to the normal level (P?0.001). While NAC addition led to a significant increase in GSH levels of the liver, heart, spleen, brain and ovarium tissues compared to both control and irradiation groups, it caused a significant decrease in the kid-ney tissue compared to irradiation group (P?0.001). As a result of NAC addition, a significant decrease was determined in spleen GSH-Px activity, heart and ovarium SOD activity compared to control and irradiation groups (P?0.05). It can be asserted that GSH increasing by the addition of NAC is the main antioxidant that has a role in decreasing oxidative stress occurring as a result of irradiation. In the examination of MDA values, it was found that the addition of NAC pro-tected the kidney and brain against the oxidative damage induced by irradiation but NAC addition could remain insuffi-cient for the liver.
Keywords: Tıbbi Araştırmalar Deneysel; Fizyoloji; Biyokimya ve Moleküler Biyoloji